Beating the Slowdown in Zambia : Reducing Fiscal Vulnerabilities for Economic Recovery - Smith, Gregory; Davies, Fiona; Chinzara, Zivanemoyo (World Bank, Washington, DC, 2016)
Policy makers in commodity-exporting countries have faced increasing challenges in the past two years, in the face of reduced demand from China and uncertain economic recovery in developed economies. Zambia is no exception. Falling copper prices and a power crisis have contributed to an economic slowdown. The effects of the slowdown could arguably have been counteracted in a sustainable manner by utilizing fiscal buffers, but this option was not available, as Zambia did not make savings or provide for stabilization measures when the economy was prospering. Furthermore, options to access external financing are limited, as Zambia’s debt levels have soared in recent years following repeat non-concessional borrowing, making it more difficult and expensive to borrow from international debt markets. This policy note examines Zambia’s fiscal vulnerabilities and the costs associated with its expansionary, subsidy-oriented fiscal policy. It then sets out the benefits of coordinating fiscal policy with monetary policy in a way that is mutually reinforcing and beneficial to private sector investment, instead of having the two pull in opposite directions, as is currently the case. Finally, it makes recommendations to help shift the fiscal position to a more sustainable path and in turn improve market confidence and the prospects for sustainable economic recovery.